2022
DOI: 10.35848/1347-4065/ac528d
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of channel mobility in 4H-SiC trench MOSFET by inducing stress at SiO2/SiC gate interface

Abstract: To investigate the impact of stress at the SiO2/SiC gate interface on the channel mobility of 4H-SiC trench MOSFETs, we fabricated trench MOSFETs with two variations of stress in channel region by changing the deposition temperature of polycrystalline silicon used for gate electrodes. The results found that effective mobility was enhanced by several dozen MPa of tensile stress induced by the polycrystalline silicon. Based on the temperature dependence of mobility, all scattering mobilities were enhanced. It wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…They have reported that compressive stress improves mobility due to lighter effective mass. 23,24) However, the tensile stress on 4H-SiC has not received much attention.…”
mentioning
confidence: 99%
“…They have reported that compressive stress improves mobility due to lighter effective mass. 23,24) However, the tensile stress on 4H-SiC has not received much attention.…”
mentioning
confidence: 99%